Selective ribosome profiling as a tool to study the interaction of chaperones and targeting factors with nascent polypeptide chains and ribosomes - Becker, Annemarie; Oh, Eugene; Weissman, Jonathan S.; Kramer, Günter; Bukau, Bernd (Nature protocols, 2013)
A plethora of factors is involved in the maturation of newly synthesized proteins, including chaperones, membrane targeting factors and enzymes. Many factors act co-translationally through association with ribosome-nascent chain complexes (RNCs), but their target specificities and modes of action remain poorly understood. We developed selective ribosome profiling (SeRP) to identify substrate pools and points of RNC engagement of these factors. SeRP is based on sequencing mRNA fragments covered by translating ribosomes (general ribosome profiling (RP)), combined with a procedure to selectively isolate RNCs whose nascent polypeptides are associated with the factor of interest. Factor-RNC interactions are stabilized by cross-linking; the resulting factor-RNC adducts are nuclease-treated to generate monosomes, and then they are affinity purified. The ribosome-extracted mRNA footprints are converted to DNA libraries for deep sequencing. The protocol is specified for general RP and SeRP in bacteria. It was first applied to the chaperone trigger factor (TF) and is readily adaptable to other co-translationally acting factors, including eukaryotic factors. Factor-RNC purification and sequencing library preparation takes 7-8 d, and sequencing and data analysis can be completed in 5-6 d.
Gesehen am 17.11.2020